Quo Vadis Penegakan Hukum Bermartabat: Kritik Terhadap Penegakan Hukum Berlandaskan Stigma No Viral No Justice - Muammar, Muammar (PAMALI: Pattimura Magister Law Review, 2024)
Introduction: The emergence of the law enforcement phenomenon based on the stigma of no viral no justice gives a bad image to the face of Indonesian law enforcement, because it leads to a form of law enforcement that is no longer dignified. As a result, the victims must use it in the form of viralizing the case they are experiencing so that they can rally the external power of the public.Purposes of the Research: This paper aims to analyze and examine a number of points that are the basis for law enforcement criticism based on the stigma of no viral no justice.Methods of the Research: This paper uses normative legal research methods. The approaches used are conceptual approaches, theoretical approaches and analytical approaches.Results / Main Findings: Law enforcement based on the stigma of no viral no justice in recent years has tarnished the face of Indonesian law enforcement. In fact, this condition has "legitimized" law enforcement to no longer be dignified because it is not in accordance with the principles of law enforcement as it should be. This paper offers three basic criticisms of the form of law enforcement with these conditions, including: first, the occurrence of deviations from the principle of equality before the law. The law no longer views the position of each legal subject as equal and equal without discrimination, but rather views whether the case is viral or not; second, the shift and change of the basic meaning of legality from no crime without criminal acts, to no crime without the virality of criminal acts/no crimes without going viral first; Third, the enforcement of the stigma of no viral no justice drags the goal of the law in obscurity to arrive at its noble mission in realizing justice, legality and legal certainty.